Penyalahgunaan Akun Netflix Oleh Pihak Kedua Di Media Sosial Di Tinjau Dari Undang-Undang Nomor 28 Tahun 2014 Tentang Hak Cipta dan Undang-Undang Nomor 11 Tahun 2008 Tentang Informasi dan Transaksi Elektronik - Tatu Afifah; Rai Indah Nurhidayah (JURNAL HAK : Kajian Ilmu Hukum, Administrasi Negara, dan Komunikasi, 2025)
One of the social media platforms that is currently widely used for buying and renting various objects is the Instagram application. With the large number of products available, including accounts for premium applications like Netflix, there are instances of social media accounts engaging in abuse by selling or renting out premium application programs on Instagram, such as the account named "digprem.store." Based on this phenomenon, the issues in this research are formulated as follows: what is the legality of renting out premium Netflix accounts by a second party through online shop services, and what are the legal consequences of renting out premium Netflix accounts through online shops according to Law Number 28 of 2014 concerning Copyright and Law Number 11 of 2008 concerning Information and Electronic Transactions. The researcher employs a qualitative method with a normative legal approach. The type of research used is normative research, which involves studying, observing, and analyzing several theoretical aspects. Data collection techniques include interviews and literature studies. The results of this study indicate that online shop services have committed a breach of contract against the provisions set by Netflix in the terms of use under clause 4.2, Article 17, Article 32 paragraphs (1) and (2) of Law Number 11 of 2008 concerning Information and Electronic Transactions, and Article 113 paragraphs (3) and (4), Article 114 of Law Number 28 of 2014 concerning Copyright.